PREDIKSI INTERAKSI MOLEKUER CAPE DENGAN IL-2, CD25, IL-10, CTLA-4, IDO, TGFβ, and CCL2 DENGAN SOFTWARE DOCKING MOLEKULER - Zauhani Kusnul (SAINTEKBU, 2019)
The use of herbal medicine as a nutritious ingredient to treat various diseases is still mostly done traditionally based on hereditary information. The development of technology supports the exploration of natural materials as a nutritious material with various scientific evidences. The development of computational and bioinfrmatic technology simulates interactions between various active compounds and target molecules virtually commonly known as molecular docking, a virtual screening based on structure used to predict the interaction of three-dimensional structures of small molecules (compounds) with the target molecular structure. Propolis is a substance produced by bees from resins collected from plants and combined with wax and secretions from bee salivary glands which are rich in various enzymes. In the world of medicine, propolis has been used since time immemorial and until now it has been known that propolis can be a natural medicine with anti-bacterial, anti-tumor, antioxidant and immunomodulatory abilities. Molecular docking between one of the active compounds in propolis, namely caffeic acid phenethyl ester (CAPE) with various target molecules such as IL-2, CD25, IL10, TGFβ, CTLA-4, CCL21, and IDO using the DockingServer software provides information that CAPE has inhibitory activity against IL-2, CD25, IL-10, CTLA-4, IDO, TGFβ, and CCL2 so that it has the potential to be further developed as a candidate for immunomodulatory therapy.